Comparative Study of Various Kinetic Models on Leaching of NCA Cathode Material - Soraya Ulfa Muzayanha; Cornelius Satria Yudha; Luthfi Mufidatul Hasanah; Linggar Tungga Gupita; Hendri Widiyandari; Agus Purwanto (Indonesian Journal of Chemistry, 2020)
The kinetics study of NCA leaching in the HCl system was proposed. Various kinetic models such as shrinking core, logarithmic rate law, and Avrami equation were used to find out the most appropriate kinetic models for this process. The effect of HCl concentrations, leaching temperatures, solid to liquid (S/L) ratio, and leaching duration were observed. The optimum conditions of NCA leaching were at HCl concentration of 4 M, temperature of 80 °C, S/L ratio of 100 g/L, and leaching time of 1 h. The result shows that shrinking core model with diffusion control process of residue layer describes well the leaching mechanism in this research, which is indicated by the good fitting of coefficient values of correlation (R2) and confirmed by the activation energy values of Ni, Co, Al that were less than 40 kJ/mol.